Parque eco-productivo para la población Raizal Wii-Mii-Kun (2020)
A development of the master plan is generated in the Amazon and Orinoquia region, in the department of Guaviare, the main objective of this project is to enhance this department at an environmental, economic and social level through the connection of the 4 municipalities, the which are: San José del Guaviare, Miraflores, the return and Calamar, proposing some strategic operations the necks are based on restitution, connectivity and the environment, in this way a partial plan is proposed in the department of Calamar in which It seeks to generate a node of transition and environmental protection, likewise three main nuclei are generated in which the different worlds of the Nukak are represented, where we find the Bak nucleus that means the world below and is characterized by being the productive nucleus, the next nucleus is the Jee which is the world which focuses on social issues, and finally we find the nucleus of the Hea, which is the nucleus of p social and environmental protection, which represents heaven for the Nukak Maku tribe, in this unit of action the architectural project Wii Mii Kun is developed, which translates into the Nukak language of us for you, this project is based on an eco park productive which is for the root protection, which seeks to boost the Squid economy with the production of artisan chocolate, respecting the ancestral customs of these tribes.